2020
DOI: 10.1101/2020.05.08.084954
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antibody neutralization of an influenza virus that uses neuraminidase for receptor binding

Abstract: Influenza virus infection elicits antibodies against the receptor-binding protein hemagglutinin (HA) and the receptor-cleaving protein neuraminidase (NA). Because HA is essential for viral entry, antibodies targeting HA often potently neutralize the virus in single-cycle infection assays. But antibodies against NA are not potently neutralizing in such assays, since NA is dispensable for single-cycle infection. Here we show that a modified influenza virus that depends on NA for receptor binding is much more sen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Indeed, antibodies may have various functions, 16 and although neutralisation is a correlate of protection for many viral diseases, 17 not all antibodies that bind a virus will neutralise it. For a given antigen, antibodies may neutralise (e.g., influenza hemagglutinin), bind the antigen on the virus surface and thereby perhaps slow the spread of infection without being neutralising (e.g., influenza neuraminidase), 18 or in some instances even enhance the infection (e.g., dengue virus). 19 Noval et al 20 recently showed that the antibody isotype diversity against SARS-CoV-2 was associated with differential serum neutralisation capacities in 101 convalescent patients.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, antibodies may have various functions, 16 and although neutralisation is a correlate of protection for many viral diseases, 17 not all antibodies that bind a virus will neutralise it. For a given antigen, antibodies may neutralise (e.g., influenza hemagglutinin), bind the antigen on the virus surface and thereby perhaps slow the spread of infection without being neutralising (e.g., influenza neuraminidase), 18 or in some instances even enhance the infection (e.g., dengue virus). 19 Noval et al 20 recently showed that the antibody isotype diversity against SARS-CoV-2 was associated with differential serum neutralisation capacities in 101 convalescent patients.…”
Section: Discussionmentioning
confidence: 99%
“…Neutralization was measured against the virus containing H3 from the A/Aichi/2/1968 virus with two mutations, Y98F and G379W, carrying GFP in the PB1 segment, and all other internal genes from A/WSN/33. The neutralization assays were performed in MDCK-SIAT1-CMV-PB1 cells using this GFP-expressing virus as described previously [ 36 , 37 , 38 , 39 ]. As with spike pseudotyped lentivirus neutralization assays, the curves were plotted and IC50s were calculated using the neutcurve Python package.…”
Section: Methodsmentioning
confidence: 99%
“…Neutralization was measured against virus containing H3 from A/Aichi/2/1968 virus with two mutations Y98F and G379W, carrying GFP in the PB1 segment, and all other internal genes from A/WSN/33. The neutralization assays were performed in MDCK-SIAT1-CMV-PB1 cells using this GFP-expressing virus as described previously [ 36 39 ]. As with Spike pseudotyped lentivirus neutralization assays, curves were plotted and IC50s were calculated using the neutcurve Python package.…”
Section: Methodsmentioning
confidence: 99%